A CROSS-SECTIONAL SURVEY TO ASSESS SOCIO-CULTURAL FACTORS INFLUENCING THE UTILIZATION OF ASRH SERVICES IN TONG PING AREA JUBA, SOUTH SUDAN. - Nanzira, Noelah (Student’s Journal of Health Research Africa, 2023)
Background: Studies have documented poor outcomes of the utilization of ASRH services especially in poor countries mostly those affected by complex emergencies. Although estimates from 2020 indicate some improvement in RMNCAH in South Sudan, utilization of ASRH services in Tong Ping remained poor due to socio-demographic, socio-cultural, and community-related factors. The study examined the sociocultural determinants influencing the utilization of ASRH services in the Tong Ping area, Juba South Sudan. Methodology: a cross-sectional survey research design whereby 177 adolescents (18-19 years) were interviewed. Quantitative data was organized and analyzed through the utilization of the Statistical Package for Social Sciences and findings were presented using the percentage tables. Bivariate and Multivariate analyses were used to identify factors that categorically and jointly influence the utilization of ASRH. Result: The study established that active peer education increased the utilization of ASRH with a significant threshold of P=0.049. A significant association was established between knowledge of family planning methods among adolescents and utilization of AHS (P=0.001). The study further found out that there are limited or no public health facilities to provide ASRH in Tong Ping which led to expensive utilization. Community perception of reproductive health services was positively associated with utilization (P=0.049). Conclusion: Younger adolescents are inquisitive and have been adequately reached with SRH information and services. Utilization of SRH has been hampered because the assumed users are compromised. This means adolescents have limited knowledge about the use of Reproductive Health. Health care is usually sought more in critical conditions than preventive. Recommendation: There should be active sensitization to increase awareness of service provisions, more training of adolescents, equipment available in health facilities with trained personnel and other resources, and the establishment of a health center around the Tong Ping area to bring free services closer to the communities and encourage peer education.